Improving care for co-occurring psychological health and substance use disorders : an implementation evaluation of the Co-Occurring Disorders Clinician Training Program - Hepner, Kimberly A.; Ayer, Lynsay; Venkatesh, Brinda; Farmer, Carrie M. (Research report (Rand Corporation), 2015)
This report presents results of an implementation evaluation of a clinician training program to improve care for Navy personnel with co-occurring disorders. Clinicians saw a need for such training and viewed it positively. Results also suggest that careful planning and targeting training towards programs best suited to treating co-occurring disorders would improve training effectiveness and likely translate into higher-quality care.